Moving towards "Cashlessness" in an emerging economy: A case study of latest policy steps in India - Manjira Dasgupta (Deutsche Bundesbank, 2017)
On November 08, 2016, India took a decisive step towards going “cashless” by suddenly announcing withdrawal of its existing currency notes of two highest denominations, namely, the Rs. 500/= and the Rs. 1000/=. The move, announced with a suddenness that took the entire nation by surprise, had at its root the purpose of countering the threefold menaces of rampant corruption, counterfeit money and cross-border and internal terror funding. It has generated widespread controversy, the main criticism being that while the policy intent was sound, the execution plan was rather unsound. With one of the highest cash-GDP ratio in the world (close to 11%), India was revealed by RBI (Reserve Bank of India) data as having a staggering share of nearly 86% held in Rs.500/= and 1,000/= notes in the currency stock in circulation (end of FY 2014-15). The cost of “retiring” this volume of currency was therefore, going to be enormous which, as economists like former World Bank Chief Kaushik Basu (Basu 2016) emphasize, could far exceed the gains. In view of the intriguing developments overtaking the Indian economy since the date of submission of the initial abstract, problems that subsequently emerged as considerably more pressing and pertinent have been treated in greater detail in this study. Consequently, the approach and methodology has been substantially modified, although of course retaining the original motivation. With its laudable objectives of striking at the cash-corruption link, India saw, within the first four days of the announcement of demonetization, a staggering surge in bank deposits exceeding USD 52 billion, leading to high hopes of trapping unaccounted or illegal money through this route, a hope that was unfortunately to be belied. Given the enormous problem of Non-Performing Assets plaguing Indian Banks, we have also paid special attention to this potential vast source of unaccounted money in some detail. Next, an overview of India's vast informal sector has been given, and the guidelines by Schneider and Williams (2013) and Schneider and Buehn (2008) have been used in an attempt to estimate the shadow economy in India using cointegration in a MIMIC framework. Finally, not only did India's decision to demonetize have enormous economic or financial implications, but it also has had huge social and political ramifications that must be recognized.
Keywords: E26; E42; E58; E65; G00; O17; 330; India; Demonetization; Cashlessness; Informal Sector; Shadow Economy